Effects of Service Quality, Customer Trust and Customer Religious Commitment on Customers Satisfaction and Loyalty of Islamic Banks in East Java - Hidayat, Rachmad; Akhmad, Sabarudin; Machmud, Machmud (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2015)
The purpose of the present study was to describe the relationships among service quality, customer trust and customer religious commitment on customer satisfaction and loyalty of Islamic banks in East Java. Respondents were Islamic banks’ customers domiciled in East Java. A predetermined number of samples were taken by the use of a simple random sampling technique. Analysis was performed using the Structural Equation Modeling (SEM). Results indicated that service quality and customer trust of Islamic banks jointly had significant effects on customer satisfaction. Service quality and customer trust had direct and indirect effects on customer loyalty mediated by satisfaction of Islamic banks’ customer in East Java. Religious commitment had no direct and indirect effect on customer satisfaction and customer loyalty.DOI: 10.15408/aiq.v7i2.1681